1968
DOI: 10.1172/jci105828
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between glomerular filtration rate and sodium reabsorption by the proximal tubule of the rat nephron

Abstract: We have tested two of the hypotheses proposed to explain the adjustment in sodium reabsorption in the proximal tubule that follows a change in the rate of glomerular filtration (glomerulotubular balance). Using the recollection micropuncture technique, we were able to measure the immediate and late changes in reabsorptive rate after an acute alteration in filtration rate produced by aortic constriction and release of constriction. It was found that fractional reabsorption, as measured by the inulin tubule flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
54
2
1

Year Published

1969
1969
2013
2013

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 19 publications
8
54
2
1
Order By: Relevance
“…Water was available ad lib. They were anesthetized with Inactin (100 mg/kg), placed on a heated micropuncture table, and prepared for study in a manner previously described (11). Indwelling polyethylene catheters were placed in the left jugular vein for infusion of inulin and furosemide, into the right jugular vein for injection of Lissamine green, and into the left femoral artery for periodic sampling of blood and measurement of arterial pressure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water was available ad lib. They were anesthetized with Inactin (100 mg/kg), placed on a heated micropuncture table, and prepared for study in a manner previously described (11). Indwelling polyethylene catheters were placed in the left jugular vein for infusion of inulin and furosemide, into the right jugular vein for injection of Lissamine green, and into the left femoral artery for periodic sampling of blood and measurement of arterial pressure.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent micropuncture study of the effect of elevated ureteral pressure on fractional sodium reabsorption by the proximal tubule in the rat ( 11), it was found that unless special care was taken to prevent retrograde flow of tubule fluid from more distal sites, the calculated value for fractional sodium reabsorption was elevated spuriously. This artifact results from the collection of fluid from more distal sites along the nephron where, as a result of continued water reabsorption, the inulin concentration is higher.…”
mentioning
confidence: 99%
“…It is possible therefore that a lower dose of ET-3 may elicit intrarenal vasodilation without affecting the overall renal vascular resistance, which results in an increase in GFR. The observed increase in FENa induced by a high dose of ET-3 might have reflected the glomerulotubular balance to some degree [ 12]. However, we consider that the pressure natriuresis which is thought to be caused by the increase in the hydraulic pressure in a peritubular capillary in consequence of the high perfusion pressure following the infusion of a high dose of ET-3 mainly increase the FENa, since there was no change in the perfusion pressure and FENa after infusion of the vehicle or a low dose of ET-3.…”
Section: Discussionmentioning
confidence: 94%
“…Dirks, Cirksena, and Berliner (3) found in the dog that fractional reabsorption was suppressed after volume expansion, and that this reduction persisted when filtration rate was lowered below hydropenic levels by arterial clamping. Other investigators, however, have found that fractional reabsorption during saline diuresis tends to return toward hydropenic levels after aortic constriction in the rat (16)(17)(18). Second, the change in total GFR is not of a sufficient magnitude to explain the change in fractional reabsorption (3,15).…”
Section: Discussionmentioning
confidence: 97%